Motor and social development of children diagnosed with Autism Spectrum Disorder submitted to physical activities and communication skills (Research, Society and Development, 2022)
Autism Spectrum Disorder (ASD) is a disorder in which the affected individual manifests changes in their development, among them, difficulties in communication and, as a consequence, also in social interaction. The severity of this neurodevelopmental disorder depends on the degree of autism diagnosed therefore it varies with each patient. That said, the objective of this study is to search the literature for works that have used interventions of physical activities and communicative skills in children with ASD, in order to punctuate the positive aspects in the development of these patients, involving gains in motor skills or communication/social interaction. The bibliographic consultation was performed through a manual search in the databases Latin American and Caribbean Literature on Health Sciences (LILACS), Scientific Electronic Library Online (SciELO), National Library of Medicine (PubMed/Medline) and PhysiotherapyEvidenceDatabase (PEDro). The nine articles included in the qualitative synthesis presented some behavioral measurement scale for autism, whether to assess motor or communication skills or even the degree of autism presented by each child. So that at the end of the study, a survey of the gains or not gains could be made, with the activities proposed to the group. Noting, therefore, that the practice of physical activity with these autistic children has an important relevance in the resourcefulness and maintenance of their motor skills, such as activities involving communication. Although different interventions were carried out, both obtained equivalent results. It can then be said that these bring considerable benefits to autistic individuals.